The Effects of Online Nudging on Individuals' Behaviour: The Case of Pokémon Go - Alnemer, Sarah (Université d'Ottawa / University of Ottawa, 2026)
The use of nudging in online advertising to subtly align the offering of products and services with individuals' identity is a now commonplace practice. Cheney-Lippold (2017) and Zuboff (2019) criticize online nudging for operating behind closed doors, cycling through of user data and personal information to modify individuals' behaviour for commercial gain. Nudging is a central feature of the popular game Pokémon Go. It uses predictive algorithms and players' geolocational data to create augmented reality gaming scenarios that guide users through real-world public and private spaces as they seek to achieve game-related objectives. As such, Pokémon Go offers an ideal microcosm for analyzing users' awareness of online nudging and other behavioural modification techniques employed in online advertising. Using a qualitative research design, semi-structured interviews were conducted with 23 undergraduate students from the University of Ottawa who self-identify as regular players of Pokémon Go to examine how they understand, navigate, and respond to the nudging practices employed in the game. The observations emerging from an analysis of their descriptions of typical gameplay sessions offer an empirical basis, albeit of limited strength, for challenging assertations that nudging practices are foremost manipulative, exploitative, or somehow disempowering. Likewise, the emerging observations about the diverse ways in which individuals interpret their encounters with nudging practices suggest possible grounds for reimagining how the understanding of data literacy might be approached.
Keywords: nudging; surveillance capitlism; pokemon go; behavioural data; online identity; algorithmn; privacy; awareness online; digital identity; data practices